Fetal MRI Characteristics of Exencephaly: A Case Report and Literature Review - Ali Sharif; Yihua Zhou (Case Reports in Radiology)
We present the fetal MRI characteristics of exencephaly, a rare malformation of the cranium. The fetus was initially misdiagnosed as anencephaly at 14 weeks of estimated gestational age (EGA) and later mislabeled as acrania at 20 weeks of EGA by ultrasound. A confirmatory magnetic resonance imaging (MRI) at 29 weeks of EGA demonstrated findings consistent with exencephaly, which was confirmed after birth. To our knowledge, no full fetal MRI characteristics have been described. We hope to use this case to review the key MRI findings in differentiating exencephaly from other cranial vault defects and to help early diagnosis of exencephaly as the appropriate use of correct nomenclature allows better research while giving parents the most accurate and appropriate counseling.